2007
DOI: 10.1097/wad.0b013e3181461932
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Depression in Individuals With Pathologic But Not Clinical Alzheimer Disease are Lower Than Those in Individuals Without the Disease: Findings From the Baltimore Longitudinal Study on Aging (BLSA)

Abstract: The prevalence of major depression is increased in Alzheimer disease, but currently the basis of this association remains unclear. The present study examined rates of depression in four groups: (1) cognitively normal controls with no Alzheimer pathology at autopsy, (2) cognitively normal individuals with Alzheimer pathology, (3) clinical diagnoses of MCI plus Alzheimer pathology, (4) clinical diagnoses of dementia plus Alzheimer pathology. Participant data were obtained from the Baltimore Longitudinal Study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
6
0
2
Order By: Relevance
“…Depressive symptoms were assessed using the Center for Epidemiologic Studies-Depression Scale. Individuals with Alzheimer’s pathology but without cognitive decline had significantly lower rates of depression than cognitively normal individuals with no Alzheimer’s pathology and individuals with Alzheimer’s pathology plus clinical diagnosis of dementia (Morgan et al, 2007). In a population-based study, 1241 participants, aged 62–85 years, were asked about their physical activity during their early adult years.…”
Section: Differences In Cognitive Agingmentioning
confidence: 99%
“…Depressive symptoms were assessed using the Center for Epidemiologic Studies-Depression Scale. Individuals with Alzheimer’s pathology but without cognitive decline had significantly lower rates of depression than cognitively normal individuals with no Alzheimer’s pathology and individuals with Alzheimer’s pathology plus clinical diagnosis of dementia (Morgan et al, 2007). In a population-based study, 1241 participants, aged 62–85 years, were asked about their physical activity during their early adult years.…”
Section: Differences In Cognitive Agingmentioning
confidence: 99%
“…A second clinical study focused on the rates of depressive symptoms in individuals with asymptomatic AD [34]. The prevalence of major depression is increased in AD, but the basis of this association remains unclear.…”
Section: Clinical Studies Of Preclinical/asymptomatic Alzheimer’s Dismentioning
confidence: 99%
“…A recent U.S. study concluded that 22% of adults over the age of 71 might have MCI (Plassman et al, 2008). Since the number of new cases of Alzheimer’s Disease (AD) is expected to increase 3-fold to 13.2 million by 2050, the development of preventive interventions is urgent (Hebert, Scherr, Bienias, Bennett, & Evans, 2003; Morgan et al, 2007). …”
mentioning
confidence: 99%